PERAN PEKERJA SOSIAL DALAM MENGEDUKASI MANTAN PECANDU NARKOBA - Ratna, Ratna; Rustiyarso, Rustiyarso; Salim, Izhar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe title of this research is The Role of Social Workers in Educating Former Drug Addicts (Studies in Bumi Khatulistiwa Pontianak Community Based Social Rehabilitation Institute). The research method used is descriptive method with a qualitative research form. The data source of this study is the social worker in Bumi Khatulistiwa Pontianak Community Based Social Rehabilitation institute. Data collection techniques in this study are through interviews, observations, and documentation, while the data collection that used are observation guides, interview guides and documentation. The analysis in this study was presented in a descriptive qualitative manner using 3 informants. The results are The role of social workers in educating former drug addicts in Bumi Khatulistiwa Pontianak Community Based Social Rehabilitation institute with the addition of knowledge by holding professional seminar activities aimed at providing knowledge about drugs, and holding religious sessions to provide religious knowledge to resident;The role of social workers in educating former drug addicts in Bumi Khatulistiwa Pontianak Community Based Social Rehabilitation institute with additional skills by carrying out morning meetings and wrap-up activities for residents to train them to interact properly. Meanwhile, to make residents able to express their opinions clearly, social workers carry out resident seminar activities to bring one topic presented in front of another resident.Â Keywords :Social Workers, Rehabilitation, DrugsÂ